Clinical and Mycological Spectrum of Chromoblastomycosis: a Case Series - Ariani, Tutty; Rizal, Yosse; Veroci, Rahma Ledika (Journal of Pakistan Association of Dermatologists, 2023)
Background: Diagnosis of chromoblastomycosis is often delayed for multiply reasons; poor degree of clinical suspicion or confusion with similar condition due to its polymorphic features and difficulties of confirmed laboratory examination. The case series aims for describing clinical appearance and mycological examination variation of chromoblastomycosis. Cases: We reported four cases of chromoblastomycosis with different type of clinical appearance. Each case appeared with different morphology; verrucous-type, tumor-type, plaque-type and mixed type. All patient had history of contact with soil, multiple trauma and chronic course of disease. Diagnosis of chromoblastomycosis in all cases were confirmed by finding sclerotic bodies in either potassium hydroxide or histopathology examination, the fungal of culture of all cases are suitable of the growth of Fonsecaea pedrosoi. All cases were treated by pulse dose itraconazole 400mg daily for a week every month. Discussion: Chromoblastomycosis is fungal infection caused by pigmented fungi acquired usually by inoculation of the skin as part of occupational or environmental hazards. It is found in immunocompetent host; all cases had no history of comorbidity. As the verrucous-type is the common type, chromoblastomycosis often misdoubt with tuberculosis cutis verrucose, as like our first case. Microscopic detection of sclerotic bodies is important and four cases here confirmed the diagnosis by its finding. Fonsecaea pedrosoi is the most common cause of chromoblastomycosis, detected in the first three cases. Itraconazole and terbinafine are the choice anti-fungal either pulse dose or daily dose.